PROGRAM STRATEGY OF HARD NEWS ON KOMPAS TV - Rahayu, Sri; Sugihartono, R.A. (Capture : Jurnal Seni Media Rekam, 2018)
This study describes the problem about the strategy of hard news program conducted by Kompas TV. The object of this research is the hard news program on Kompas TV which is examined by using qualitative descriptive approach. The sampling technique used in this research is purposive sampling. Methods of data collection using participative observation, interviews, and literature study. The results of the study show that the strategy undertaken by producers and programming team in Kompas TV includes strategy in program planningconsisting of program product arrangement, and program promotion. Strategy in self production (in house production) and program purchase through three systems. The strategy on program execution involves broadcasting the program according to the broadcast pattern and in accordance with the target audience. In addition, the program supervision strategy is conducted through internal control quality by the producer and programming team that refersto Broadcasting Behavior Guidelines and Broadcast Program Standards (P3SPS) and external supervision by Indonesian Broadcasting Commission (KPI), as well as strategies that are compiled through daily and weekly evaluation.